Tracing local wisdom in the integration of ethnomathematics in vocational high school mathematics education: A Scopus systematic review - Dhema, Magdalena; Cholily, Yus Mochamad; Rahardjanto, Abdulkadir (Indonesian Journal of Science and Mathematics Education, 2025)
Integrating ethnomathematics into mathematics learning in vocational high schools is an innovative strategy to connect mathematical concepts with local cultural contexts. This study is grounded in the urgency of preserving local wisdom through education and the need for contextual learning approaches relevant to vocational students. The research aims to explore how local wisdom is integrated into mathematics instruction through an ethnomathematics perspective, based on a systematic review of Scopus-indexed literature. Employing the PRISMA-based Systematic Literature Review (SLR) method, this study identifies, screens, and analyzes articles published in the last ten years. The findings reveal that applying ethnomathematics in vocational mathematics classrooms enhances conceptual understanding, fosters cultural identity, and creates a more meaningful learning environment. Additionally, this approach encourages teachers to design culturally responsive and locally relevant learning strategies. The study highlights the importance of equipping teachers with the skills to develop ethnomathematics-based materials and calls for supportive educational policies that promote the inclusion of local culture in the curriculum. These insights contribute to the growing body of literature on contextualized education and demonstrate the potential of ethnomathematics to preserve cultural heritage while improving mathematics learning outcomes in vocational education settings.